The Effect of Purun Tikus (Eleocharis dulcis) and Organic Material Addition in Constructed Wetland Systems on the Improvement of Acid Mine Drainage Quality - Simamora, Eprilia; Nurcholis, Mohammad; Ardian, Aldin; Ernawati, Rika; Winarno, Eddy (Universitas Pembangunan Nasional (UPN), 2024)
Coal mining activities often cause environmental challenges, one of which is acid mine drainage (AMD) with low pH and elevated concentrations of heavy metals and suspended solids. This study aimed to assess water quality improvement through a constructed wetland system using Purun tikus (Eleocharis dulcis) and palm oil empty fruit bunch compost (TKKS). Laboratory-scale experiments were conducted with five treatment variations and three replications over a 20-day retention period. Results indicated that the media combination, with or without limestone addition, significantly altered the water quality parameters. The pH increased from 3.35 to 7.76; TSS decreased from 1,373.3 mg/L to 151 mg/L; Fe decreased from 33.15 mg/L to 2.68 mg/L; and Mn decreased from 7.06 mg/L to 0.45 mg/L over 20 days. These results indicate the potential of constructed wetlands using native plants and organic materials as an environmentally friendly strategy for treating mining wastewater.